The final particles of wenyan (based on the novel of pu songling «miss ying-ning, or the laughing girl»). (Journal of Oriental Studies, 2016)
The article is devoted to the final particles, which used to replace the punctuation in classical Chinese. The study carried out on novel «Miss Ying-Ning, or The laughing girl» of Chinese writer Pu Sunlin into theappropriate languages.
Keywords: wenyan; translation; the final particle; syntactic words; punctuation